2021
DOI: 10.3390/d13060230
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomics Analysis Reveals the Microbial Communities, Antimicrobial Resistance Gene Diversity and Potential Pathogen Transmission Risk of Two Different Landfills in China

Abstract: In this study, we used a metagenomic approach to analyze microbial communities, antibiotic resistance gene diversity, and human pathogenic bacterium composition in two typical landfills in China. Results showed that the phyla Proteobacteria, Bacteroidetes, and Actinobacteria were predominant in the two landfills, and archaea and fungi were also detected. The genera Methanoculleus, Lysobacter, and Pseudomonas were predominantly present in all samples. sul2, sul1, tetX, and adeF were the four most abundant antib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…For example, Haan utilized the CARD to evaluate ARGs related to the thawing of frozen soil in inland Alaska [24]. The CARD was also applied to the analysis of the transmission risk of ARGs in landfills and ARG pollution after sewage irrigation [25,26]. Zhong et al, by using the CARD, found that the levels of ARGs were significantly reduced in strain-enhanced biogas residue composting [27].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Haan utilized the CARD to evaluate ARGs related to the thawing of frozen soil in inland Alaska [24]. The CARD was also applied to the analysis of the transmission risk of ARGs in landfills and ARG pollution after sewage irrigation [25,26]. Zhong et al, by using the CARD, found that the levels of ARGs were significantly reduced in strain-enhanced biogas residue composting [27].…”
Section: Introductionmentioning
confidence: 99%
“…Abbreviated references have been provided and the raw input data used to generate this figure can be found in File S4 . Data obtained from (in chronological order): (7, 11, 14, 15, 1719, 21, 22, 32, 34, 49, 8893).…”
Section: Resultsmentioning
confidence: 99%
“…Metagenomics has allowed valuable insights into the physiological pathways contributing to waste degradation including cellulose metabolism (28, 29) and plastic biodegradation (30). Metagenomics has also been used to address human health concerns tied to landfills such as the occurrence of antibiotic resistance in pathogens found in MSW (31, 32). Genome-resolved metagenomics (33) has the potential to connect methanogenic lineages to the substrates that can support methane production within a given landfill environment (34).…”
Section: Introductionmentioning
confidence: 99%
“…Archaeology is increasingly becoming a focus of genetic investigations [22][23][24]. Thus, special soil bacterial communities have been reported in archaeological excavation sites-prehistoric buildings, settlement places, and tombs [25][26][27][28][29][30]-and medieval or early modern pre-industrial mining and smelting sites [31][32][33][34]. Despite the investigations of soil bacterial communities on modern and historical metal mines and smelting sites, less attention has been paid to historic coal mines.…”
Section: Introductionmentioning
confidence: 99%